2020
DOI: 10.3390/ani10112093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation of Garlic and Oregano Essential Oil on Biomarkers of Oxidative Status, Stress and Inflammation in Postweaning Piglets

Abstract: The effects of two different concentrations of micro capsuled oregano essential oil (OEO) and purple garlic powder on biomarkers of oxidative status, stress, and inflammation, as well as on average daily gain (ADG) and feed conversion ratio (FCR), were evaluated in piglets during the postweaning period. The trial was carried out with 300 crossbred pigs of 21 days of age fed with different concentrations of OEO and purple garlic powder and ZnO. Saliva and serum samples were taken to evaluate a panel of biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 75 publications
4
16
0
Order By: Relevance
“…At this time, with the current knowledge we could provide the following ideas about the interpretation of the markers of redox homeostasis: The values of biomarkers of redox homeostasis in saliva change in some physiological conditions such as farrowing and lactation. Although reference ranges should be established with larger populations and the values could change depending on the assays used and therefore these values should be interpreted with caution; in our experience, the mean values that we usually obtain in the saliva of healthy adult animals are between 0.1–0.5 mmol/L for TEAC, CUPRAC and FRAS, 30–200 μmol/L for AOPP and 5–25 μmol/L for H 2 O 2 [ 27 , 63 , 64 ]. …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…At this time, with the current knowledge we could provide the following ideas about the interpretation of the markers of redox homeostasis: The values of biomarkers of redox homeostasis in saliva change in some physiological conditions such as farrowing and lactation. Although reference ranges should be established with larger populations and the values could change depending on the assays used and therefore these values should be interpreted with caution; in our experience, the mean values that we usually obtain in the saliva of healthy adult animals are between 0.1–0.5 mmol/L for TEAC, CUPRAC and FRAS, 30–200 μmol/L for AOPP and 5–25 μmol/L for H 2 O 2 [ 27 , 63 , 64 ]. …”
Section: Discussionmentioning
confidence: 98%
“…Moreover, other antioxidants such as uric acid and catalase can be measured. In addition, oxidant biomarkers such as advanced oxidation protein products (AOPP) and hydrogen peroxide (H 2 O 2 ) can be quantified in porcine saliva [ 63 , 64 ]. The origin of these analytes in saliva is unclear, and only CUPRAC showed a significant positive correlation between saliva and plasma values, being this correlation low [ 63 ].…”
Section: Evaluation Of the Redox Homeostasismentioning
confidence: 99%
“…Different studies reported that they could inhibit the growth of pathogenic microorganisms by causing conformational changes in cell membranes to become less impermeable ( 5 ). Subsequently, growth-promoting effect ( 6 ), anti-diarrhea ( 7 ) and anti-oxidant function ( 8 ), microbial homeostasis regulation ( 9 ), etc., have been found to attract extensive attention of animal nutritionists.…”
Section: Introductionmentioning
confidence: 99%
“…Plant secondary metabolites, mainly essential oils, have been widely used in monogastric animals to provide nutritional regulation. They enhance growth phenotype ( 10 ), feed digestibility ( 11 ), and reduce diarrhea rate and oxidative stress ( 8 , 12 ), particularly in piglets and broilers. However, the application of these materials in ruminants has been limited because of their complex digestive system.…”
Section: Introductionmentioning
confidence: 99%
“…Pigs fed a diet of 0.2% oregano essential oil had decreased expression of NF-κB and STAT3, transcription factors involved with inflammation (Cappelli et al, 2021). On the other hand, pigs fed a diet of over 0.4% oregano essential oil had increased CRP, a general measure of inflammation, while those fed below 0.4% had no change in CRP (Rivera-Gomis et al, 2020). Additionally, rats fed 200 and 400 mg of oregano extract per kg body weight per day had reduced pro-inflammatory TNF-α and liver lymphocyte infiltration .…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%